Ruminating on rudeness: Exploring veterinarians' experiences of client incivility. (9th November 2021) - Irwin, Amy; Hall, Dionne; Ellis, Hannah
Abstract: Background: Interactions with clients have been identified as a key potential stressor within veterinary practice. However, there is a lack of research investigating the experience, and impact, of specific behaviours, such as incivility. The current study aimed to address this literature gap by investigating veterinarian perceptions of client rudeness. Method: Telephone interviews ( n  = 18) were used to gather qualitative data regarding veterinarian perceptions of client rudeness. This encompassed description of an uncivil interaction, potential causes of incivility, the impact on the veterinarian and coping strategies. Results: The results indicate that veterinarians are exposed to a range of rude behaviours from clients, with suggested causal attributions spanning financial concerns, stress and worry. Adverse consequences associated with uncivil interactions included increased stress, mental health impacts and withdrawal from clients. Responses to incivility encompassed proactive pre‐planning, empathy and clear communication. Support from colleagues was important to enable reflection and coping, alongside individual strategies, such as self‐care. Conclusion: Client incivility has the potential to adversely impact veterinarians. Appraisal of potential external causes for rudeness could facilitate constructive responses to client incivility and support coping. This should be combined with emotional support from colleagues to mitigate any negative consequences following uncivil client interactions.